Higher Risk of Preterm Twin Delivery Among Shorter Nulliparous Women - Simões, T (2024)
Objective: To determine if maternal height in nulliparous women influences pregnancy results in twin pregnancies. Material and methods: Retrospective cohort analysis evaluating twin pregnancies followed at Centro Hospitalar Universitário Lisboa Central, between 1995 and 2020. Of the 2900 pregnancies followed in that period, 886 nulliparous women with dichorionic twin pregnancies were selected. Two groups were considered: A - maternal height <163 cm (<Q2) (n = 436) and B - maternal height ≥167 cm (≥Q3) (n = 234), The following results were compared: Age, body mass index (BMI), premature contractions, premature rupture of membranes (PROM), hypertensive disorders, gestational diabetes, gestational age at birth, delivery <28, <32, <34, < 36, ≥37 weeks (wks), average weight of newborns, very low birth weight, low birth weight, cesarean section rate, stillbirths, five minute Apgar score, neonatal death and perinatal death. Result(s): PTB rates decreased along increasing maternal height. The comparison between group A and group B revealed no statistically significant differences in maternal characteristics (age, mode of conception - spontaneous or ART pregnancies, or BMI). Statistically significant differences were found in mean gestational age at birth (35.1 ± 1.8 vs. 36.0 ± 2.6 wks), PTB rates < 32, 34 and 36 wks, OR: 3.2, 2.3 and 2.4 respectively, p < 0.01. Shorter women had a 1.7× and 2.6× increased risk for significantly low (<2500 g) and very low (<1500 g) newborn birth weight (BW), respectively, and a 40 % increased risk of Cesarian delivery. No significant differences were shown with respect to stillbirths, neonatal and perinatal deaths, which had a low incidence in this study. In ART pregnancies we found the same results regarding PTB rates and newborn birthweight in shorter women. In Logistic Regression analysis, maternal height <Q2 is an independent risk factor for PTB under 32, 34 and 36 wks, adjusted OR: 2.0. 2.2 and 2.4, respectively, 95 % CI 1.1-3.7, p = 0.021. Conclusion: Increased pregnancy risk in nulliparous shorter women should be taken into consideration in double embryo transfers.